Community empowerment of waste management in the urban environment: More attention on waste issues through formal and informal educations - A. Brotosusilo; D. Utari; H. Negoro; A. Firdaus; R. Velentina (Global Journal of Environmental Science and Management)
BACKGROUND AND OBJECTIVES: Indonesia's economic growth is estimated to be driven by high levels of consumption which lead to large amounts of waste. Education is required to raise environmental awareness among the population as it is one of the ways to overcome the waste issue, especially in urban areas, which are the engines of economic growth. This study aims to determine whether the higher levels of education have a greater impact on citizens regarding environmental concerns such as littering.METHODS: The study took logistics regression on the primary data survey from 7 cities (Jakarta, Jambi, Muaro Jambi, Ambon, Padang, Surabaya, and Tasikmalaya) in Indonesia during 2019-2021. The survey includes 563 observations on the household level, involving a total of 2,349 respondents. The logistic regression predicts the likelihood of urban citizens to litter, given their socio-economic backgrounds and existing littering behavior and environmental awareness.FINDINGS: This study found that education did not affect decreasing the value of littering behavior as expected since it is estimated that an increase of 1 year in school will increase the probability of littering by 0.0189. Formal education is not enough to decrease the probability of littering behavior on the individual level. In contrast, informal education taught on keeping a clean environment matters is better than conventional formal education. Besides that, having self-initiative on environmental caring and good habits from childhood will decrease the probability of littering on an individual level. An individual has a self-initiative, the probability of littering will be 0.1732 times lower than those who do not have self-initiative. This study also found that per capita income and per capita expenditure in big cities in Indonesia ranged between USD 156,903 and USD 116,857. These economic factors affect the behavior of citizens not to litter. The per capita expenditure increasing by USD 1 per person per day will decrease the probability of littering by -0.0468. However, these factors are not enough to minimize the littering behavior since the disposal place availability becomes another keys factor in decreasing littering behavior on urban citizens.CONCLUSION: The government should also focus on building citizens' behavior regarding waste management awareness especially building good habits since childhood and individual initiative, simultaneously implementing the programs to reduce waste production.